Literatur Review Potensi Kompor Tenaga Matahari Sebagai Sumber Energi Alternatif - Anugrah Budi Wicaksono; Sahid Ramandhani (Aptek, 2026)
The increase in Indonesia's population has led to a rise in demand for natural resources, resulting in a negative impact on wildlife. To maintain energy security, alternative energy sources must be explored, one of which is solar energy. One such source is harnessing solar energy using a concentrated solar power (CSP) system on solar stoves. Research has shown that solar radiation generates heat as an energy source that can be concentrated into a single point, enabling water to be boiled using a device called a parabolic mirror reflector. The heat generated can then be used to heat water. The method used in this study was a literature review. Based on the authors' research, it can be concluded that solar energy can be utilised as an alternative energy source in solar stoves, thereby reducing the use of fossil fuel energy in the form of gas, namely Liquid Petroleum Gas (LPG), which is not environmentally friendly.